An exploratory investigation into faculty motivation to publish: a study of business school faculty in India. (1st January 2013) - Kumar, Payal; Israel, D.
A survey was conducted amongst the faculty of the top business schools of India, to compute a model based on factor loadings, with faculty research publication as the dependent variable. This study shows that faculty in general assign importance to self motivation and to the extrinsic rewards of research grants and job security, while for IIM faculty peer pressure is the main motivating factor to publish. It was also found that years in academics and seniority in rank are favourable to faculty research publication. This study indicates that the lack of 'publish or perish' pressure on faculty in India is linked to the dearth of faculty research publications, and it is suggested that the higher education system needs to be reformed so as to incentivise and motivate faculty to publish more.